Pre-season fitness testing in elite soccer: integrating the 30-15 Intermittent Fitness Test into the weekly microcycle - Buchheit, M.; Brown, M. (Sport Performance & Science Reports, 2020)
Fitness testing is an important part of the pre-season player screening process (1).Depending on cultures and preferences, various submaximal or maximal tests are used in soccer, including continuous linear (e.g., treadmill tests, Vam-Eval (2)), continuous non-linear (20-m shuttle test (3)) or intermittent non-linear (e.g., Yo-Yo (4) and 30-15 Intermittent Fitness Tests, 30-15 IFT (5)) protocols. Among these, the 30-15 IFT remains the only test that can mimic the physiological demands of most team and racketsports, and be used i) as a performance measure (peak test running speed, VIFT) (6), ii) to assess a players' locomotor profile (7) and iii) to improve high-intensity interval training (HIIT) prescription (8, 9). There is however little consensus concerning the optimal timing of the 30-15 IFT programming,i.e., when is the best time to implement the 30-15 IFT within the pre-season phase?